Earthen architecture : past, present and future, proceedings of the International Conference on Vernacular Heritage, Sustainability and Earthen Architecture, Valencia, Spain, 11-13 September 2014 /: past, present and future, proceedings of the International Conference on Vernacular Heritage, Sustainability and Earthen Architecture, Valencia, Spain, 11-13 September 2014. ([2015]) - Unknown
No abstract available